IMPLICATIONS OF THE 'MARRIAGE IS SCARY' TREND ON TIKTOK ON MUSLIM TEENAGERS' VIEWS ON MARRIAGE - Rambe, Rizki Zil Ikram; Iwan (Awang Long Law Review, 2025)
The growing phenomenon of "Marriage is Scary" on social media, particularly on TikTok, has influenced Muslim teenagers in Medan Johor's views on marriage. The trend highlights fear and ambivalence towards marriage with negative narratives that focus on the burdens and challenges of marriage. This study aims to explore the impact of these trends on Muslim teenagers' perceptions, as well as the relevance of religious understanding and the role of social media in shaping attitudes towards marriage. The method used is juridical sociological with a qualitative approach, collecting data through interviews, questionnaires and observation. The Legal Benefit Theory in this study shows that law can serve as an instrument that not only protects individuals from the impact of misperceptions, but also ensures social welfare in the long run. The results show that this trend has an impact on the decline in teenagers' interest in marriage, the increase in hedonistic behavior and individualism, and the shift in family values. On the other hand, a strong religious understanding can be a protective factor against these negative influences. In conclusion, it is important for families, schools and religious communities to improve media literacy and provide contextualized religious guidance to strengthen the understanding of marriage in Islam as an act of worship that brings blessings, as well as to counterbalance the negative narratives that develop on social media.